Pengaruh Penyuluh Agama Islam Terhadap Pernikahan Usia Dini Di Kecamatan Kelekar - Ela Susana; Candra Darmawan; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "The Influence of Islamic Religious Counselors on Early Marriage in Kelekar District". The aim of this study was to determine the effect of Islamic religious instructors on reducing the number of early marriages in Kelekar District. This type of research uses a quantitative approach. The data sources used are primary data and secondary data. The collection techniques used in this study were questionnaires and documentation. Sampling was carried out using a sampling technique, namely the sampling technique for all members of the population used as a sample, amounting to 33 people. The analysis technique used in this research is quantitative analysis with validity test, reliability test, basic assumption test (data normality test, linearity test, homogeneity test), and simple linear regression analysis and hypothesis testing (t test and coefficient of determination test). The results of this study indicate that there is an influence of Islamic religious instructors on early marriage, this is evident from the results of data processing using SPSS version 25 which obtains a t value greater than t table with a value of (2.603> 0.344) with a significance value of 0.000 <0 ,05. This is also the magnitude of the coefficient of determination or R of 0.424 which indicates that there is an influence of Islamic religious instructors on early marriage of 42.4%, while the remaining 57.6% is influenced by other variables not included in the research variables, such as the environment, residents, Education, etc. Keywords: Islamic Religious Counselor, Early Marriage.